Ground plan for performing Emergency Surgery in suspected and confirmed COVID-19 patients - Tarun Singhal (Shiraz University of Medical Sciences, 2020)
Background: Covid-19 crisis has created a huge challenge to the healthcare systems all over the world. Different health policies have been adopted with variable success. This paper aims to provide a practical pathway of managing surgical patients in current Covid-19 pandemic. Methods: A modified framework of local policy and pathways is suggested to deal with acute surgical admissions and semi-emergency conditions. This included logistic changes in the hospitals' infrastructures, staff allocations and the use of suitable personal protection equipment. Results: The introduction of the suggested changes is expected to improve the delivery of the services and reduce risks to patients and the staff. About 80 operations were conducted since the application of these changes. Conclusion: Challenges with Covid-19 pandemic has required each health system to adequately respond to the crisis by the introduction of an urgent fundamental change to the current surgical practice and is likely to change the management and local policies of each hospital after the crisis.